Online Immunization Class during the Covid–19 Pandemic - Santi Agustina; Kusmayra Ambarwati; Ismail Sangadji; Irma Ariyanti (UKInstitute, 2023)
Conditions in the world even Indonesia is experiencing the Covid 19 pandemic which has become a health condition. By implementing strict health protocols, people are currently encouraged to stay at home. This aims to break the chain of the spread of Covid 19. The existence of these regulations makes parents' mothers increasingly dilemma in providing vaccination needs to their children. They need to make direct contact with health workers. Therefore, many children are late to vaccination. In fact, it has been known that vaccination is the main service that can prevent pain in children. Therefore, vaccination services must still be provided in accordance with government-regulated protocols. This activity aims to provide comprehensive information, eliminating the dilemma of the community, especially parents, about how and protocols to vaccinate children during the Covid 19 pandemic. This activity was attended by more than 400 participants with the majority of participants from Java Island. The results of this activity are known that this education is useful in increasing participants' knowledge in carrying out basic vaccinations on their children during the Covid 19 pandemic. Abstrak: Kondisi di dunia bahkan Indonesia sedang mengalami pandemi Covid 19 yang menjadi maslah kesehatan. Masyararakat saat ini dihimbau untuk tetap di rumah saja, dengan menerapkan protokol kesehatan yang ketat. Hal tersebut bertujuan agar dapat memutus mata rantai penyebaran Covid 19. Adanya peraturan – peraturan ini, membuat ibu orang tua semakin dilema dalam memberikan kebutuhan vaksinasi kepada anaknya. Mereka perlu melakukan kontak langsung kepada tenaga kesehatan. Oleh karena itu, banyak anak yang mengalami terlambat melakukan vaksinasi. Padahal, telah diketahui bahwa vaksinasi adalah pelayanan utama yang dapat mencegah kesakitan pada anak.Oleh karena itu pelayanan vaksinasi harus tetap diberikan sesuai protokol yang telah diatur pemerintah. Kegiatan ini bertujuan untuk memberikan informasi menyeluruh, menghilangkan dilema masyrakat terutama orang tua, mengenai cara dan protokol melakukan vaksinasi pada anak di masa pandemi Covid 19 ini. Kegiatan ini diikuti lebih dari 400 peserta dengan mayoritas peserta dari Pulau Jawa. Hasil dari kegiatan ini diketahui bahwa edukasi ini bermanfaat dalam meningkatkan pengetahuan peserta dalam melaksanakan vaksinasi dasar pada anak mereka pada masa pandemi Covid 19.